First report of fruit rot on cantaloupe caused by Fusarium equiseti in Thailand - Wipornpan Nuangmek (2019)
© 2019, The Phytopathological Society of Japan and Springer Japan KK, part of Springer Nature. Fruit rot is one of the most important diseases of cantaloupe. In June 2016, fruit rot was found in cantaloupe fruit (Cucumis melo var. cantalupo) in Phayao Province, Thailand. The causal fungus was isolated from lesions and identified as Fusarium equiseti based on both morphological characteristics and phylogenetic analysis of combined sequences of the internal transcribed spacer of ribosomal DNA, translation elongation factor 1-alpha and β-tubulin genes. Cantaloupe fruit inoculated with the isolated fungus developed symptoms similar to natural ones in the field. This is the first report of cantaloupe fruit rot caused by F. equiseti in Thailand.